Detecting TYMS Tandem Repeat Polymorphism by the PSSD Method Based on Next-generation Sequencing - He, Binsheng; Yang, Jialiang; Tian, Geng; Bing, Pingping; Lang, Jidong (Current Bioinformatics, 2020)
Background: Thymidylate Synthase (TS) is an important target for folic acid inhibitors such as pemetrexed, which has considerable effects on the first-line treatment, second-line treatment and maintenance therapy for patients with late-stage Non-Small Cell Lung Cancer (NSCLC). Therefore, detecting mutations in the TYMS gene encoding TS is critical in clinical applications. With the development of Next-Generation Sequencing (NGS) technology, the accuracy of TYMS mutation detection is getting higher and higher. However, traditional methods suffer from false positives and false-negatives caused by factors like limited sequencing read length and sequencing errors. Objective: A method was needed to overcome the short sequencing read length and sequencing errors of NGS to make the detection of TYMS more accurate. Methods: In this study, we developed a novel method based on
Keywords: Paired Seed Sequence Distance (PSSD)